1985
DOI: 10.1530/acta.0.1100408
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of somatostatin on meiotic maturation of cultured porcine follicular ova

Abstract: To investigate the physiological importance of somatotrophin release-inhibiting factor (SRIF), effects in vitro of synthetic SRIF 14 on germinal vesicle breakdown (GVB) of cultured porcine follicular ova were studied. The proportion of ova with GVB decreased gradually and significantly with increasing concentrations of SRIF 14 in the range from 6 \m=x\ 10\m=-\12 to 6 \m=x\ 10\m=-\7 m during a 22 h period of culture. The inhibitory effect was apparent for the period between 14 and 22 h in the course of culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Our observation of dose-dependent stimulation of meiotic maturation by SRIH contrasts with the inhibi¬ tion reported in the porcine ovary by Mori et al (4).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observation of dose-dependent stimulation of meiotic maturation by SRIH contrasts with the inhibi¬ tion reported in the porcine ovary by Mori et al (4).…”
Section: Discussioncontrasting
confidence: 99%
“…female, somatostatin-like immunoreactivity has been detected in porcine ovary (3), where it has been shown to inhibit germinal vesicle breakdown (4). In the one reported study in the rat (5), no effect of somatostatin on germinal vesicle breakdown was demonstrated, but only a small number of oocytes were studied.…”
mentioning
confidence: 97%
“…As more and more pro-hormones, hormones (and their mRNAs, Einspanier et al, 1986) are discovered in the ovary some may be candidates as recently mentioned for the SRIF (pig, Mori et al, 1985) and for the anti-mullerian hormone (AMH) (rat, Takahashi et al, 1986 Lintern-Moore, 1978 ;Kaplan et al, 1982 ;Bachvarova et al, 1985). After the growth period a low rate of RNA synthesis is maintained, even if nucleolus compaction indicates that rRNA transcription is impaired.…”
mentioning
confidence: 99%